Il come di una ermeneusi pedagogica. Dialogo e metodo per comprendere l'altro - Cosimo Costa (Firenze University Press, 2017)
With the intent to understand pedagogical hermeneutics is capable to create a proper connection with school, tradition, dialogue and is therefore able to avoid the risks of de-formation and in-formation, this article looks into two schools of thoughts: those of Gadamer and Betti. In the context of education to sensitivity and recovery of tradition, the philosophical hermeneutics of these two authors provides a methodology for an ethically and theoretically-based educational dialogue, able to "stimulate" consciousness and responsibility in those who "choose" to face, confront and meet the other.